Peningkatan Kompetensi Guru MGMP Matematika SMA Melalui Pelatihan Penyusunan Bank Soal Digital Berbasis Website - Rike Marjulisa; Ayunda Putri; Yusa Putra; Devan Aptinsyah; Nanditya Syahmi Khan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Digital transformation in education requires teachers to adapt to learning and assessment technologies. This community service program aims to improve the competence of high school mathematics teachers in Pelalawan Regency through training in the use of a digital question bank website. Activities include orientation, training in question development, use of automatic evaluation features, and utilization of the student learning outcome analysis dashboard. Data was collected through observation, questionnaires, and documentation of teachers' activities during training and implementation. The results of the activities indicate that teachers are able to operate the website effectively. The automatic evaluation feature was proven to speed up the correction process and provide faster feedback to students. Meanwhile, the analysis dashboard made it easier for teachers to monitor student learning achievements based on topics, thereby supporting measurable improvements in learning strategies. Additionally, the digital question bank helped standardize question quality across schools under the coordination of the MGMP, making assessments more consistent and transparent. The implementation of this website also improves time efficiency and reduces teachers' administrative burden in the evaluation process. Thus, this program contributes to improving teachers' digital literacy, assessment effectiveness, and strengthening collaboration among teachers within the MGMP environment. The sustainability of the program is expected to support the creation of an inclusive and competitive digital learning ecosystem.